DIRECTIONS OF INFLUENCE OF HIGHER EDUCATION PARAMETERS ON ECONOMIC GROWTH IN UZBEKISTAN - Nabiyev , Dilmurod; Anopchenko , Tatiana; Cherepovitsyn, Alexey; Ochilov, Akram (THE INNOVATION ECONOMY, 2023)
In addition to human resources and capital, continuing education, in particular higher education, has a significant impact on the economic growth of the Republic of Uzbekistan. Accordingly, the article is considered the problems, advantages of higher education and innovative systems, as well as their role in stimulating economic growth in Uzbekistan. According to the results of the study, it was shown that the number of highly qualified personnel in the country is associated with economic growth. The relationship between higher education and economic growth in the Republic of Uzbekistan was determined using regression analysis, which took into account the growth of GDP and the number of graduates as an independent variable, the cost of per graduate and the average year of study established for the training of highly qualified personnel.